Aberrant natural killer (NK) cell activation and dysfunction among ART-treated HIV-infected adults in an African cohort - Nabatanzi, R; Bayigga, L; Cose, S; Rowland-Jones, S; Canderan, G; Joloba, M; Nakanjako, D (Elsevier, 2019)
BACKGROUND:We examined NK cell phenotypes and functions after seven years of ART and undetectable viral loads (<50 copies/ml) with restored CD4 T-cell counts (≥500 cells/μl) and age-matched healthy-HIV-uninfected individuals from the same community. METHODS:Using flow-cytometry, NK cell phenotypes were described using lineage markers (CD56+/-CD16+/-). NK cell activation was determined by expression of activation receptors (NKG2D, NKp44 and NKp46) and activation marker CD69. NK cell function was determined by CD107a, granzyme-b, and IFN-gamma production. RESULTS:CD56 dim and CD56 bright NK cells were lower among ART-treated-HIV-infected than among age-matched-HIV-negative individuals; p = 0.0016 and p = 0.05 respectively. Production of CD107a (P = 0.004) and Granzyme-B (P = 0.005) was lower among ART-treated-HIV-infected relative to the healthy-HIV-uninfected individuals. NKG2D and NKp46 were lower, while CD69 expression was higher among ART-treated-HIV-infected than healthy-HIV-uninfected individuals. CONCLUSION:NK cell activation and dysfunction persisted despite seven years of suppressive ART with "normalization" of peripheral CD4 counts.